Adalimumab for steroid sparing in patients with giant-cell arteritis: results of a multicentre randomised controlled trial. Issue 12 (29th July 2013) - Seror, Raphaèle; Baron, Gabriel; Hachulla, Eric; Debandt, Michel; Larroche, Claire; Puéchal, Xavier; Maurier, François; de Wazieres, Benoît; Quéméneur, Thomas; Ravaud, Philippe; Mariette, Xavier
Abstract : Objectives: To evaluate the effect of adding a 10-week treatment of adalimumab to a standardised treatment with corticosteroids on the ability to taper more rapidly corticosteroid doses in patients with newly diagnosed giant cell arteritis (GCA). Methods: Patients included in this double-blind, multicentre controlled trial were randomly assigned to receive a 10-week subcutaneous treatment of adalimumab 40 mg every other week or placebo in addition to a standard prednisone regimen (starting dose 0.7 mg/kg per day). The primary endpoint was the percentage of patients in remission on less than 0.1 mg/kg of prednisone at week 26. Analysis was performed by intention to treat (ITT). Results: Among the 70 patients enrolled (adalimumab, n=34; placebo, n=36), 10 patients did not receive the scheduled treatment, seven in the adalimumab and three in the placebo group. By ITT, the number of patients achieving the primary endpoint was 20 (58.9%) and 18 (50.0%) in the adalimumab and placebo arm, respectively (p=0.46). The decrease in prednisone dose and the proportion of patients who were relapse free did not differ between the two groups. Serious adverse events occurred in five (14.7%) patients on adalimumab and 17 (47.2%) on placebo, including serious infections in three patients on adalimumab and five on placebo. Two patients died in the placebo arm (septic shock and cancer) and one in the adalimumab group (pneumonia). Conclusions: In patients with newly diagnosed GCA, adding a 10-week treatment of adalimumab to prednisone did not increase the number of patients in remission on less than 0.1 mg/kg of corticosteroids at 6 months. Clinical trial registration number: NCT00305539.